RFID essentials, innovations and beyond - Sukula, Shiva (New Delhi : Ess Ess Publications, 2011)
Radio Frequency Identification (RFID) systems are emerging as one of the most pervasive computing technologies due to their broad applicability. RFID systems consist of tiny integrated circuits equipped with antennas (RFID tags) that communicate with their reading devices (RFID readers). This technology works using radio-frequency waves without line of sight. It has created tremendous opportunities for linking various objects in the physical world. These objects can be numbered, identified, cataloged, and tracked. RFID systems present many advantages and features that cannot be found in other ubiquitous computing environments, RFID communication is fast, convenient and its application can substantially save time, improve services, reduce labor cost, thwart product counterfeiting and theft, increase productivity gains and maintain quality standards. The present book has looked into on various topics such as RFID system Elements, Tools, Techniques and technologies behind RFID, Implementation issues of RFID, RFID and Barcode technology, RFID standards, RFID systems and solutions for library, RFID application in various arena, RFID and consumer privacy issues, near field communications and RFID in Indian and global perspectives. The topics covered are suitable for layman as well as professionals.
Keywords: Radio frequency identification systems; Radio frequency identification systems